(untitled) (Bioresearch Communications, 2024)
We are guided by our thoughts and determination. The problem of the present study was to investigate whether there is any effect of self-talking and determination on enhancing performance. The current study aimed to ascertain whether future performance is impacted by self-talking and determination. We hypothesized that in order to improve performance, self-talking and determination are beneficial. We selected 28 students from class VI and then randomly divided them into experimental and control groups. We taught the experimental participants how to apply self-talking and determination positively. Then both groups were given some tasks such as handwriting, drawing, and talking about themselves. We found that the mean scores of times spent in performance for experimental and control groups were 631.50 seconds and 521.50 seconds, respectively, which differed significantly at the .046 (α=.05) level with a t-value of 2.09 (df=26). We came to the conclusion that self-talking and determination have a favorable impact on improving performance because the experimental group performed for a significantly longer time than the control group. Bioresearch Commu. 10(2): 1553-1556, 2024 (July)